(x-1)в квадрате=(x+(-1))в квадрате

lizamrio1 lizamrio1    3   22.04.2020 14:51    4

Ответы
MATVEYPRO26 MATVEYPRO26  13.09.2020 14:22

х в квадрате + 2*х +1 , так как (х+1) в квадрате = (х+1)*(х+1) = х*(х+1) + 1*(х+1) = х в квадрате +х + х +1 = х в квадрате + 2*х +1

*-умножить

папе за решение .)

Пошаговое объяснение:

ПОКАЗАТЬ ОТВЕТЫ
BOULEVARDDEPO111 BOULEVARDDEPO111  13.09.2020 14:22

Правда

Пошаговое объяснение:

Раскрыть скобки:

(x-1)^2 = (x-1)^2

Обе части равны

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика